From the Classroom to the Screen: The Power of Artistic Expression in Effective Online Teaching and Communication - Kadagidze, Lamara (European Scientific Journal, ESJ, 2023)
The article examines the role of emotional intelligence and artistic expression in online teaching and communication, drawing from original research conducted through a survey. In the context of the increasing prevalence of online education, it is crucial to explore effective approaches that enhance student engagement and foster meaningful interactions. The findings highlight the power of artistic expression in capturing students’ attention, facilitating comprehension, and promoting creativity. Incorporating artistic expression skills, such as body language, tone, and inflection, enhances communication and engagement in the online teaching environment. The work delves into strategies for incorporating emotional intelligence and artistic expression in online teaching, providing practical tips specifically tailored for online English teaching. These strategies offer guidance on how educators can effectively utilize these elements to create dynamic and vibrant online learning environments that optimize the learning experience and promote academic success. However, the paper also acknowledges the challenges faced by educators in implementing these strategies. The research findings shed light on the hesitations and fears experienced by teachers in being recorded or teaching in front of a camera. They also highlight the need for training, resources, and guidelines to support educators in acquiring and developing artistic expression skills. By integrating artistic expression and addressing the challenges involved, teachers can create impactful and supportive online learning environments that promote student engagement, facilitate meaningful interactions, and provide an enriched learning experience in the digital era of education. The article provides valuable insights and practical recommendations for educators to enhance their online teaching practices.